Development of 3-dimensional (3D) printable construction materials - Zheng, Ye (2017)
The primary objective of this paper is to investigate the effect of various admixtures on the rheological properties (yield stress and viscosity) of mortar in 3D printing. Desired rheological properties of 3D printing mortar need to have sufficient viscosity and yield stress for good adherence between ejected layers, allowing certain build-up thickness. Beside admixtures, influence on rheological properties with the use of different sand types was also examined. One other objective is to research on the mechanical property between conventional casted concrete and 3D printed concrete. The effect of admixtures, such as fly ash, silica fume percentage (SF) by volume, sand and polyvinyl alcohol (PVA) fibres upon the rheological property of cement paste was researched. It was observed that generally the yield stress and viscosity increase with the increment of fly ash to binder ratio (Fa/c) and sand to binder ratio (s/b). Effect of increasing Silica fume percentage (SF) would increase the yield stress but decrease the viscosity. On the other hand, polyvinyl alcohol fibres percentage (PVA) by volume would decrease the yield stress but increase the viscosity. In addition, the yield stress and viscosity were found to be decreasing with increasing water to binder ratio (w/b). Impact of difference in sand size was also investigated. The results showed that sand with bigger particle size would increase spread and decrease in both yield stress and viscosity; larger sand size increases the workability/flowability of the mortar. Under tensile tests, the mechanical property of 3D casted/extruded specimens was found to have poorer performance than conventional casted specimens.